First Report on Mermithid Parasitism (Enoplea: Mermithidae) in a Southeast Asian Spider (Araneae: Araneidae) - Košulič, O; Mašová, Š (Helminthologia, 2019)
Details about the record of ajuvenile mermithid roundworm parasitizing the bark spiderCaerostris sumatrana Strand,1915 from Thailand are presented.The morphology and ecology of both organisms is discussed. Morphological features suggest this juvenile nematode belongs to the genus cf.- Aranimermis. Due to the sub adult stage of parasite, identification to species-level was not possible. This first report of a nematode infection in C. sumatrana with several recent findings from other studies significantly adds to the current inventory of mermithids parasitizng spiders. Moreover, our finding is among the first record of this host-parasite interaction from Southeast Asia.
Keywords: Agamomermis; Thailand; Aranimermis; Caerostris sumatrana; orb-web spider; parasitoid